Fractal theory modeling for interpreting nuclear and electrical well logging data and establishing lithological cross section in basaltic environment (case study from Southern Syria). (May 2017) - Asfahani, Jamal
Abstract: Fractal theory modeling technique is newly proposed in this research for interpreting the combination of nuclear well logging, including natural gamma ray, density and neutron-porosity, and the electrical well logging of long and short normal, for establishing the lithological cross section in basaltic environments. The logging data of Kodana well, localized in Southern Syria are used for testing and applying the proposed technique. The established cross section clearly shows the distribution and the identification of four kinds of basalt which are hard massive basalt, hard basalt, pyroclastic basalt and the alteration basalt products, clay. The concentration- Number (C-N) fractal modeling technique is successfully applied on the Kodana well logging data in southern Syria, and can be used efficiently when several wells with much well logging data with a high number of variables are required to be interpreted. Highlights: Testing and applying fractal theory modeling technique on the nuclear and electrical well logging data of Kodana well in Southern Syria. Using Concentration-Number (C-N) approach while applying fractal geometry. Differentiating between four kinds of basalt. Establishing the lithological section of the studied well.